A brief review on analysis and recent development of parabolic trough collector - Bappa Mondal; Ambarish Maji (Energy Storage and Saving)
Currently, conventional energy sources, such as coal and petroleum, are gradually being depleted because of their excessive usage and atmospheric pollution. Therefore, alternative energy sources have been discovered to reduce pollution and satisfy escalating energy needs. This type of energy can be harnessed from natural sources, and it is known as renewable energy. Solar energy is a renewable energy source. The most common method for accumulating solar energy is the use of solar collectors. Based on the accumulation method, solar collectors can be divided into focused and concentrated. Parabolic trough collectors (PTCs) are a type of concentrating solar collector in which a solar beam is reflected by a parabolic reflector and accumulates at the outer surface of the absorber tube. The fluid flowing through the inner surface of the tube carries heat and either stores it or uses it for different purposes, such as cooking, industrial heating, and room heating. Many studies have assessed PTC system performance. The performance of a PTC depends on different factors, such as the collector surface, collector material, receiving tube, type of fluid carrying the heat, incident angle, and wind load. Many studies have been conducted to improve these parameters and PTC efficiency. Moreover, the use of metal foam absorbers in the receiver tube reduces heat loss by 45%. Molten salt as a heat-transfer fluid results in 70.5% increase in thermal efficiency, and Cu nano-fluid yields a 5% increase in receiver efficiency. In addition, tubes exhibit 25% higher performance than steel tubes. The modified fiber-glass-reinforced PTC exhibits 70% efficiency. In addition, graphene oxide nanofluid has been considered the best fluid to enhance photovoltaic thermal performance. This paper presents a brief review of the various techniques and findings of relevance.